Students’ Motivation and Affection Profiles and Their Relation to Mathematics Achievement, Persistence, and Behaviors - Xiao, Feiya; Sun, Li (Frontiers in Psychology, 2021)
Objective: We aimed to explore profiles of subgroups of US students based on their motivational and affective characteristics and investigate the differences in math-related behaviors, persistence, and math achievement across profiles. Method: We used 1464 US students (male 743 51%, female 721 49%, age 15.82±0.28) from PISA 2012 US data in our study. First, we employed latent profile analysis and secondary clustering to identify subgroups of students based on motivational (math self-concept, interest in math, perceived control, instrumental motivation) and affective factors (math anxiety). Next, we used regression to compare differences in math behavior, persistence, and achievement among all identified subgroups. Results: We found five distinct groups of students with different patterns of motivation and affection. The subgroup of students with the lowest math anxiety and the highest motivation levels showed the highest math achievement and levels of persistence. The groups with high math interest, math self-concept, and instrumental motivation showed the most frequent math-related behaviors. Conclusions: Our findings reveal the complexity of the students’ motivational and affective profiles. Our findings are significant for teachers and educators to understand the diversity of students and provide theoretical and practical support for individualized and differentiated instruction.